2018
DOI: 10.4236/ojrad.2018.84030
|View full text |Cite
|
Sign up to set email alerts
|

Male Breast Nodules in Ouagadougou (Burkina Faso): Radiological and Histopathological Aspects

Abstract: Objective: To describe the radiological and histological aspects of breast nodules among men in our practice setting. Methodology: This is a descriptive and retrospective study conducted from January 2014 to October 2017. The study included male patients with breast nodules classified ACR3, 4 or 5 after a mammographic and ultrasound scan. These lesions were explored through an ultrasound-guided breast microbiopsy. The following are the variables collected: age, family history of breast cancer, medical history,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Some studies have even found that ultrasound and clinical examination may be enough to decide what to do with a breast lesion in the male subject [ 18 ]. In Africa, there are a few studies on the radiopathological correlation of lesions suspected of breast cancer in men, such as that of N'timon et al [ 19 ] in Togo and Ouedraogo et al [ 20 ] in Burkina Faso. N'timon et al in their study only considered the correlation of ACR4 and 5 lesions in imaging and the histological results of ultrasound-guided microbiopsies.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have even found that ultrasound and clinical examination may be enough to decide what to do with a breast lesion in the male subject [ 18 ]. In Africa, there are a few studies on the radiopathological correlation of lesions suspected of breast cancer in men, such as that of N'timon et al [ 19 ] in Togo and Ouedraogo et al [ 20 ] in Burkina Faso. N'timon et al in their study only considered the correlation of ACR4 and 5 lesions in imaging and the histological results of ultrasound-guided microbiopsies.…”
Section: Discussionmentioning
confidence: 99%